Analysis The Determinants of Capital Structure and The Measurement of Speed of Adjustment in Manufacturing Firms Listed on Indonesia Exchange Stock - Wiyandari, Esti; Haymans Manurung, Adler (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The goal of this study is to analyze the factors affecting capital structure and the measurement of speed of adjustment of capital structure. The factors used were profitability, business risk, and investment. Financial leverage was used as a dependent variable proxied by debt-to-equity ratio. The sampling technique used was purposive sampling with 35 manufacturing firms listed on Indonesia Stock Exchange from 2017-2023. This study used panel data regression as an analytical method. The results of this study show that profitability positively affects financial leverage. Manufacturing firms of consumer goods subsector could adjust the optimal leverage less than a year. The study is expected to be a reference for management and academics.